Broadened band C-telecom and intense upconversion emission of Er3+/Yb3+ co-doped CaYAlO4 luminescent material obtained by an easy route - Perrella, R. V.; Schiavon, M. A.; Pecoraro, E. [UNESP]; Ribeiro, S. J L [UNESP]; Ferrari, J. L. (Elsevier, 2016)
This work reports on photoluminescence properties of Er3+/Yb3+ co-doped CaYAlO4 in powder form, synthesized by an easy route using citric acid as ligand to form complex precursor. The 1.2 mol% of Yb3+ was fixed, while the amount of Er3+ changed in 0.5, 1.5 and 3 mol% in order to evaluate the photoluminescence properties as a function of the Er3+ concentration. The structural and thermal properties of the viscous solutions and powder materials obtained after the heat-treatment at 1000, 1100 and 1200 °C for 4 h were evaluated by XRD, FTIR and TG/DTA analysis. The results showed the formation of pure CaYAlO4 tetragonal crystalline phase after heat-treatment at 1100 °C and 1200 °C. Intense emission in the visible region under excitation at 980 nm was attributed to upconversion process, from Er3+ intra-configurational f-f transitions. The emissions were assigned to the transitions 2H11/2→4I15/2 and 4S3/2→4I15/2 (green region), and 4F9/2→4I15/2 (red region) energy levels. The ratio between emission band integrated areas assigned to the red and green emissions increased as a function of Er3+ concentration. Under excitation at 980 nm with 100 mW of power pump, the materials also showed intense and broadening emission with maximum at 1520 nm with FWHM of 84.74 nm for the sample CaYAlO4:1.5% Er3+/1.2% Yb3+ heat-treated at 1000 °C for 4 h. The photoluminescence properties showed that these materials are promising for use in C-telecom band as optical amplifier biological marker or/and solid-state laser devices under excitation at 980 nm.
Keywords: C-telecom window; Calcium Yttrium Aluminate; Rare earths; Upconversion